En direcciones opuestas: transición demográfica y de pensiones de vejez en el Perú - Cruz-Saco Oyague, María Amparo (2006)
Explores how remittances, pensions and health care provided by Padomi, an office with the social security system, may affect the income security and well-being of old people in Peru. The demographic transition is moderate but accelerating due to a sharp drop in fertility rates, particularly in urban areas, and a rate of actual out-migration that may be larger than officially estimated by the INEI. The latter may imply that the demographic growth rate is half (0.7 percent) its reported rate (1.4 percent). Affiliation to the privately administered pension system has decreased and the national pension system is in actuarial imbalance which deters affiliation (dependency rate is 1 to 1). Thus, evasion to mandatory retirement savings will cause that by 2025, 77 percent of persons older than 65 will not have a pension. The demographic dividend that ends around 2025-30 presents an opportunity for the implementation of instruments that can help mitigate the income insecurity of older people. Further research and the use of an intergenerational approach will be needed to help inform public policy. The paper ends with a few questions for future research.